Municipal breast and colorectal–anal cancer mortality in Sardinia, Italy from 2012 to 2020: application of a hierarchical Bayesian method - Laura Maria Beatrice Belotti; Emilio AL Gianicolo; Antonello Russo (BMJ Public Health)
Background Excess mortality rates for breast cancer and colorectal–anal cancer in Sardinia are reported in the literature. The aim of the study is to analyse mortality for both cancer entities in Sardinian at municipality level.Methods Sex-specific mortality rates by region and municipality of residence were computed using data from the Italian National Institute of Statistics for the years 2012–2020. Causes of death for malignant breast cancer in women and colorectal–anal cancer in both genders were analysed. The epidemiological analysis was based on the direct and indirect standardisation method. To obtain better interpretable maps of the distribution of relative risk (RR) of mortality, the hierarchical Bayesian Poisson-Gamma method was used.Results With regard to breast cancer mortality in women, RRs showed an excess of mortality at the municipal level in four municipalities. In relation to colorectal–anal cancer, RRs showed an excess mortality in four municipalities for men and in three municipalities when considering the total population. At the health-district level, an excess mortality was observed in 1 out 24 districts for colorectal–anal cancer, in both men and the total population.Conclusion This study provides an analysis of mortality at the municipal level for breast cancer and colorectal–anal cancer in Sardinia. It is recommended that the Sardinian regional authorities act on modifiable risk factors, like increasing the screening coverages for both neoplasms, in order to reduce the burden of both diseases.